QRS complex axis deviation changing in catheter ablation of left fascicular ventricular tachycardia. Issue 11 (5th September 2020) - Zhou, Genqing; Lu, Xiaofeng; Nie, Zhenning; Chen, Songwen; Wei, Yong; Cai, Lidong; Xu, Juan; Ding, Yu; Peng, Shi; Wu, Xiaoyu; Wang, Zulu; Liu, Shaowen
Abstract: Aims: The mechanisms of the QRS complex axis deviation changing of idiopathic left fascicular ventricular tachycardia (FVT) during or after radiofrequency catheter ablation were investigated in this study, which were still not well defined. Methods and results: In the index procedure, FVTs characterized by right bundle branch block configuration and left-axis deviation (LAD-FVT) were ablated at the VT exit site guided by the earliest ventricular activation with fused presystolic Purkinje potential (PP) in 234 consecutive patients. A new type of FVT characterized by right-axis deviation (RAD-FVT) was identified after successful elimination of the LAD-FVT in 12 patients, including 9 patients during the index procedure and 3 patients during follow-up. The QRS duration of RAD-FVT was shorter than that of LAD-FVT (115.3 ± 15.2 vs. 125.3 ± 16.4 ms, P = 0.006). The RAD-FVTs showed an earliest ventricle activation site localized at anterior fascicle area in 11 patients and anterior-median fascicle area in 1. However, the earliest PP during the RAD-FVT was still identified within the posterior fascicular network. Elimination of the RAD-FVTs was successfully achieved by applying radiofrequency current at a more proximal site within the left posterior fascicular network guided by the earliest PP. After a mean of 1.6 ± 0.8 ablation procedures and median follow-up of 132 (range 19–216) months since the last procedure, no recurrence was observed in any patients. Conclusion: The axis deviation changing of QRS complex in FVT may be attributed to the different exit sites of the reentry.